Galaxy mergers in eagle do not induce a significant amount of black hole growth yet do increase the rate of luminous AGN. Issue 4 (26th April 2020) - McAlpine, Stuart; Harrison, Chris M; Rosario, David J; Alexander, David M; Ellison, Sara L; Johansson, Peter H; Patton, David R
ABSTRACT: We investigate the connection between galaxy–galaxy mergers and enhanced black hole (BH) growth using the cosmological hydrodynamical eagle simulation. We do this via three methods of analysis, investigating: the merger fraction of AGN, the AGN fraction of merging systems, and the AGN fraction of galaxies with close companions. In each case, we find an increased abundance of AGN within merging systems relative to control samples of inactive or isolated galaxies (by up to a factor of ≈3 depending on the analysis method used), confirming that mergers are enhancing BH accretion rates for at least a subset of the galaxy population. The greatest excess of AGN triggered via a merger are found in lower mass ( M * ∼ 10 10 M⊙ ) gas rich ( f gas > 0.2) central galaxies with lower mass BHs ( M BH ∼ 10 7 M⊙ ) at lower redshifts ( z < 1). We find no enhancement of AGN triggered via mergers in more massive galaxies ( M * ≳ 10 11 M⊙ ). The enhancement of AGN is not uniform throughout the phases of a merger, and instead peaks within the early remnants of merging systems (typically lagging ≈300 Myr post-coalescence of the two galaxies at z = 0.5). We argue that neither major (M_*, 1 / M_*, 2 14 ) nor minor mergers (110 M_*, 1 / M_*, 2 14 ) are statistically relevant for enhancing BH masses globally. Whilst at all redshifts the galaxies experiencing a merger have accretion rates that are on average 2–3 times that of isolated galaxies, the majority of mass that is accreted on to BHs occurs outside the periods of a merger. We compute that on average no more than 15 per cent of a BHs final day mass comes from the enhanced accretion rates triggered via a merger.